SNP microarray abnormalities in a cohort of 28 infants with congenital diaphragmatic hernia. (8th June 2015) - Stark, Zornitza; Behrsin, Joanna; Burgess, Trent; Ritchie, Anna; Yeung, Alison; Tan, Tiong Y.; Brown, Natasha J.; Savarirayan, Ravi; Patel, Neil
Abstract : Chromosomal abnormalities are an important factor in the pathogenesis of congenital diaphragmatic hernia (CDH), a relatively common congenital defect associated with high morbidity and mortality. The adoption of array‐based platforms for chromosome analysis has resulted in the identification of numerous copy number variants (CNVs) in infants with CDH, highlighting the potential pathogenic role of many novel genes. We identified a retrospective cohort of 28 infants treated for CDH at a single institution who had microarray testing to determine the proportion of microarray abnormalities and whether these were contributory to CDH pathogenesis. Eight patients (29%) had microarray abnormality. Seven (25%) were considered likely contributory to CDH pathogenesis, including two mosaic trisomy 9s, a 9q22.31q22.32 microduplication, two atypical 22q11.21 microdeletions, a 2q35q36.1 microdeletion, and a 15q11.2 microdeletion, offering insights into the genetic mechanisms underlying CDH development. © 2015 Wiley Periodicals, Inc.